CALIPERIA BREVIPES N. SP. (CILIATA: PERITRICHA), EPIZOIC ON RAJA ERINACEA MITCHILL AT SAINT ANDREWS, NEW BRUNSWICK - Laird, Marshall (Canadian Journal of Zoology, 1959)
Two adults of the common skate, or tobacco box, Raja erinacea Mitchill, trawled in Passamaquoddy Bay, N. B., in June, 1958, bore myriads of peritrichous ciliates on and about the free edges of the gill filaments. The morphology of these epibionts refers them to the genus Caliperia Laird (Scyphidiidae), previously known from a single New Zealand species. C. brevipes differs from the genotype in having relatively shorter caudal processes, a posteriorly located micronucleus, and a prominent siderophilous collar at the cytostome. Comparisons are drawn between these organisms and Ellobiophrya donacis Chatton and Lwoff.